DSS METODE AHP DAN TOPSIS DALAM PEMILIHAN RESTORAN DI KOTA PONTIANAK - Cresensia Devi (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2022)
Each region has a variety of foods and unique tastes, ranging from the type of food, the prices of various foods, the strategic location of food places to the facilities provided to attract the community. As in the city of Pontianak, there are now many restaurants everywhere. However, with the number of restaurants available, it is increasingly difficult for people to determine a restaurant based on the desired criteria. Problems arise when the menus offered on the menu list are not all available, often get complaints of long service, the taste served is not in accordance with people's expectations, the products served are sometimes not in accordance with the prices offered and there are still few references to restaurants in the city. Pontianak. In this study, the authors combine the AHP and Topsis methods to find the best restaurants in Pontianak City. The AHP method is used to calculate the weight of each criterion, while the Topsis method is used to generate preference values ​​and rank recommendation results. There are 5 (five) criteria determined, namely restaurant cleanliness, food and beverage menus, facilities, services and prices. There are 5 (five) alternative restaurants in Pontianak City, A1, A2, A3, A4 and A5. Based on the research that has been done, it can be concluded that the collaboration between the AHP-Topsis method can help decision makers in choosing the best restaurant in Pontianak City. The magnitude of the preference value obtained at each restaurant becomes a reference in the restaurant's assessment. The highest preference value as the first rank is 0.751363589 on A5.